The Influence of Using Canva-Based Video Learning Media on Learning Outcomes in Work and Simple Machines Material - Patricia Sasmita Kadir; Supartin Supartin; Abdul Haris Odja; Trisnawaty Junus Buhungo; Lukman Samatowa; Raghel Yunginger (Jurnal Pijar MIPA, 2025)
The demands of 21st-century learning require the integration of digital and interactive media, as conventional science instruction often fails to optimally engage students and improve learning outcomes. The study aims to investigate the impact of using Canva-based video learning media on students' learning outcomes in the topic "Work and Simple Machines" within the science subject. The use of Canva as a learning tool constitutes a 21st-century educational medium that can provide a more efficient learning experience. It is a learning resource that can be edited and customized according to specific needs. This research is based on the fact that the learning process in schools is still dominated by conventional methods such as lectures and discussions, which results in low student activity and learning motivation. The research design is a one-group pretest-posttest design. The sampling technique used in this study is Cluster Random Sampling. The population of this study consists of students from SMP Negeri 1 Marisa, with the sample tested being class VIII A (n = 30), designated as the experimental class. Meanwhile, the research data were collected using test instruments to determine the level of students' learning achievement. The tests used in this study include prerequisite tests (normality test), hypothesis testing, and n-gain analysis. The results of the hypothesis test indicate that the t-value in all sample classes is greater than the t-table value; thus, H₁ is accepted. Based on the n-gain analysis, a value of 0.68 was obtained in the experimental class, which falls into the high category. The statistical test used in the normality test is the Lilliefors test with a significance level set at 5% (α = 0.05). Therefore, the use of Canva-based video learning media has a significant effect on students' learning outcomes in the material on work and simple machines.